LIMA BARRETO LEITOR DE MACHADO DE ASSIS: LEITOR DE SI PRÓPRIO - LILIA MORITZ SCHWARCZ (Machado de Assis em Linha)
The main goal of this article is to elaborate a balance of the impressions, ambivalent for sure, that Lima Barreto had on Machado de Assis. This new angle on Lima Barreto as a reader of Machado can be developed through the reading of articles, letters, short stories, where Barreto explicitly or implicitly refers to Machado. The comparison between them became more radical over the years, eliding what was a kind of personal, political and literary strategy for Lima Barreto, whose goal was to find another place for himself in the republic of letters.